AN ANALYSIS OF ENGLISH DEIXIS USED IN “ LIGHT SWITCH” SONG LYRIC BY CHARLIE PUTH - Budik Kusworo (English Language Teaching Journal, 2025)
This research investigates the use of English deixis in the lyrics of "Light Switch" by Charlie Puth. As a key linguistic element, deixis is crucial for interpreting meaning in communication. The study aims to identify the types of deixis present in the lyrics and analyze their functions. Adopting a descriptive qualitative approach, the research focuses on three primary types of deixis: person deixis, spatial deixis, and temporal deixis..The findings reveal that person deixis dominates the lyrics, with a total of 70 occurrences, followed by temporal deixis (3 occurrences) and spatial deixis (2 occurrences). The frequent use of person deixis, especially the pronouns "I" and "you," suggests a strong emphasis on personal interaction and emotional expression in the song. The study concludes that deixis in song lyrics plays a significant role in conveying the intended message, emotions, and meaning. Keywords: deixis, song lyric, pragmatics.